Chemical sensors : simulation and modeling - Korotchenkov, G. S. (Gennadii Sergeevich) (New York : Momentum Press, 2012)
This is the fifth of a five-volume comprehensive reference work that provides computer simulation and modeling techniques in various fields of chemical sensing. The important applications for chemical sensing include such topics as bulk and surface diffusion, adsorption, surface reactions, sintering, conductivity, mass transport, and interphase interactions.
vol. 1. Microstructural characterization and modeling of metal oxides - vol. 5. Elektrochemical sensors.
Includes bibliographical references and and index.
Keywords: Chemical detectors; Electrochemical sensors